2013
DOI: 10.1371/journal.pone.0063437
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Ligand-Binding Region of Borrelia hermsii Fibronectin-Binding Protein

Abstract: Many pathogenic microorganisms express fibronectin-binding molecules that facilitate their adherence to the extracellular matrix and/or entry into mammalian cells. We have previously described a Borrelia recurrentis gene, cihC that encodes a 40-kDa surface receptor for both, fibronectin and the complement inhibitors C4bp and C1-Inh. We now provide evidence for the expression of a group of highly homologues surface proteins, termed FbpA, in three B. hermsii isolates and two tick-borne relapsing fever spirochete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 50 publications
1
25
2
Order By: Relevance
“…The binding affinities of human and bovine fibronectin for recombinant BHA007 of ϳ20 to 30 nM were comparable to those for fibronectin-binding proteins in Gram-positive cocci, including F2 of Streptococcus pyogenes and FnBPA of Staphylococcus aureus (56-59). Brenner et al reported that BHA007 and its orthologs in B. turicatae and B. parkeri bound to fibronectin but neither C4b-binding protein nor C1 esterase inhibitor (60). They mapped the ligand-binding site for the B. hermsii protein by using blotting assays with human fibronectin in serum and RF Borrelia fibronectin-binding protein deletion mutants and made use of a spontaneous mutant of bha007 that encoded a polypeptide lacking the C-terminal half of BHA007 (60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding affinities of human and bovine fibronectin for recombinant BHA007 of ϳ20 to 30 nM were comparable to those for fibronectin-binding proteins in Gram-positive cocci, including F2 of Streptococcus pyogenes and FnBPA of Staphylococcus aureus (56-59). Brenner et al reported that BHA007 and its orthologs in B. turicatae and B. parkeri bound to fibronectin but neither C4b-binding protein nor C1 esterase inhibitor (60). They mapped the ligand-binding site for the B. hermsii protein by using blotting assays with human fibronectin in serum and RF Borrelia fibronectin-binding protein deletion mutants and made use of a spontaneous mutant of bha007 that encoded a polypeptide lacking the C-terminal half of BHA007 (60).…”
Section: Discussionmentioning
confidence: 99%
“…Brenner et al reported that BHA007 and its orthologs in B. turicatae and B. parkeri bound to fibronectin but neither C4b-binding protein nor C1 esterase inhibitor (60). They mapped the ligand-binding site for the B. hermsii protein by using blotting assays with human fibronectin in serum and RF Borrelia fibronectin-binding protein deletion mutants and made use of a spontaneous mutant of bha007 that encoded a polypeptide lacking the C-terminal half of BHA007 (60). Depending on the RF Borrelia species, the fibronectin-binding domains within these proteins were mapped somewhere between amino acid positions 180 and 230 in the unprocessed polypeptides with the signal peptides (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bind human and various animal C4BP (143, 148, 149, 157, 158). A comprehensive analysis identified outer surface proteins (Osps) associated with C4BP including OspA, Vlps, variable membrane proteins (Vmps), and several unidentified Osps (159).…”
Section: Inhibition Of the Mammalian Complement System By Borrelia Anmentioning
confidence: 99%
“…However, as the binding of these components or regulators to borrelial proteins occurs on the spirochete surface, lysing the cells prior to incubation may change the structure of borrelial proteins and prevent binding. This may explain some inconsistent results when analyzing the complement regulator-binding activity of borreliae using this method (Table 1 ; Hartmann et al, 2006 ; McDowell et al, 2006 ; Rogers and Marconi, 2007 ; Bhide et al, 2009 ; Grosskinsky et al, 2010 ; Brenner et al, 2013 ).…”
Section: Approaches To Study Mechanisms Of Serum Resistance Factors Imentioning
confidence: 99%